A question to the President of the United States, Donald Trump: is it a travel ban, or a Muslim ban, or a travel Muslim ban? - Arafa, Mohamed (Revista de Investigações Constitucionais, 2018)
Recently, the United States Supreme Court passed a victory to the current President Donald J. Trump by revitalizing parts of a travel ban on individuals from six Muslim-majority countries that he alleged is needed for national security and the interests of the United States but that adversaries criticize and claim as biased and discriminatory. The justices lessened the scope of lower court decisions that had entirely blocked crucial parts of a March 6, 2017 executive order that Trump had said was required to avert terrorism attacks, permitting his temporary ban to go into effect for folks with no strong ties to the United States. In this domain, the court issued its order on the last day of its current term and agreed to hear oral arguments again at a later stage, so it can decide lastly whether the ban is legitimate in a foremost test of presidential powers and controls.